Improvement of family caregiversâ knowledge of polypharmacy in the elderly after health education - Mustaming, Mustaming; Loriana, Rina; Azhari, Azhari; Badar, Badar (Pharmaciana, 2018)
The different health problems in elderly patients require complex management. However, if the use of medicines is uncontrolled, it will lead to polypharmacy. This study aimed to analyze the effect of health education on family caregiversâ knowledge of polypharmacy particularly to prevent drug therapy problem in elderly patients. This quasi-experimental study used one-group pre-test post-test design. The population was family caregivers who had elderly members in their care and lived within the working area of Bengkuring Public Health Center. The population members were selected according to the inclusion criteria until a minimum sample size was reached. Having met the criteria, the respondents were asked to fill in a pre-test questionnaire before they partook in the health education for polypharmacy and a post-test questionnaire after their participation. The pre-test and post-test information were then analyzed using a paired t-test. This study revealed that the family caregiversâ knowledge of polypharmacy improved by 32.5% with a probability value (p= 0.000< 0.001) less than the level of significance (5%). The contribution of the health education to the family caregiversâ knowledge of polypharmacy was 74.3%. There was an improvement in the family caregiversâ knowledge of polypharmacy after participating in the health education.